Access 2003 bible - Prague, Cary N. (Wiley Pub., 2004)
The most comprehensive reference on this popular database management tool, fully updated with the new features of Access 2003 including increased use of XML and Web services Explores the new, tighter integration with SharePoint and BizTalk in Office "X" that enables greater flexibility for gathering and manipulating data. Written by an international bestselling author team with several books to their credit, including previous editions of Access Bible. Gets Access beginners started with hundreds of examples, tips, and techniques for getting the most from Access. Offers advanced progra.